The Effectiveness of Reading Al-Qur'an Surah Al-A'la on Short Term Memory - Anggraini, Putri; Apriliani, Liza; Prasetyaningtyas, Pingkan Visionari; Merdiaty, Netty (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
The aim of this research is to find out whether reading the Al-Qur'an is effective on short-term memory. Using a quasi-experimental research method with one group pretest-posttest design. The subjects of this research were 16 female students at one of the SMP in Cibitung. The results of the research found that there is effectiveness in reading Al-Quran surah Al-A'la on short term memory, this can be seen in the results of the t test which obtained a t value of 2,739 with a t table of 2,119 which shows that t count > t table. By knowing the effectiveness of reading the Koran on short term memory, it is hoped that readers will be able to implement it in their daily lives.